Pengaruh Set Back Terhadap Kinerja Batas Layan Struktur Dengan Soft Storey Akibat Beban Gempa - Muhammad Nur Fajar; Mizwan Purnama; Albertus Didik Setyo Purwantoro; Herlina Arifin; Alfina Maysyurah (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
The development times have been accompanied by an extremely quick development, which brought architectural features like geometric imperfections and soft store buildings. Buildings having high earthquake risk in Sorong have challenges due to an active fault.. This study's goal was to identify the relationship between displacement and drift ratio and structural performance in high-rise structures with and without set backs. Using structural analysis software, the building was modeled in this study with a maximum of 7 stories and a total height of 37 m. Seismic forces were also analyzed using reflection spectroscopy of various responses. Buildings with soft storey effects without set backs and buildings with soft storey effects with set backs are the two types under study. According to the research, soft store buildings with set backs produce the highest displacement and drift ratio outcomes when compared to soft store buildings without set backs. Based on the service limits' performance under earthquake loads, it is still within safe bounds.